Characterization of redox and salinity-tolerant alkaline protease from Bacillus halotolerans strain DS5 - Wen, Yangxuan; Qiang, Jiyu; Zhou, Guixu; Zhang, Xiaobo; Wang, Lei; Shi, Yawei (Frontiers in Microbiology, 2022)
Bacillus halotolerans DS5 was isolated and identified as a halophilic microbe according to 16S rRNA analysis and the physical and chemical indices of the strain. A new alkaline protease (designated as prot DS5) from Bacillus halotolerans DS5 was produced, purified, and characterized. After 12 h incubation in the medium with 1% dextrin, 0.5% NaCl, 2% soluble starch, and 1% yeast extract (pH 7.0), it could reach the maximum enzyme activity (279.74 U/ml). The prot DS5 was stable in the pH range of 6.0–12.0 and the temperature range of 40–60°C, with maximal hydrolytic activities at pH 9 and at 50°C. In the presence of Ca2+, Mn2+, Ba2+, Mg2+, and Fe3+, protease activity was enhanced. The prot DS5 was maintained highly stable in NaCl (up to 2.5 mol/L), reducing and oxidizing agents. The prot DS5 also exhibited compatibility in other detergent ingredients, such as non-ionic and anionic surfactants. These properties of prot DS5 make this enzyme suitable for various industrial applications (e.g., detergents and leather).